Effect of photo-biomodulation therapy in decreasing postoperative pain after surgical removal of third molars compared to other treatment therapies: a systematic review - Ganguly, Shreya; Das, Asish K.; Burman, Subhasish; Maji, Abhijit; Khatua, Abhishek (International Journal of Research in Medical Sciences, 2024)
Post-operative pain, discomfort, and trismus are common postoperative complications after surgical extraction of third molars. Various therapeutic approaches like prescribing analgesic drugs, corticosteroids, and Non-steroidal anti-inflammatory drugs are followed to reduce these complications. Photo-biomodulation therapy (PBMT) utilizes a monochromatic light source that shows effects in all phases of inflammation by reducing edema, redness, heat, and pain. In vivo studies were searched to evaluate postoperative pain levels in patients who underwent photo-biomodulation therapy following extraction of impacted third molars. A comprehensive search was done from January 2023 to July 2023 in PubMed electronic databases. In addition, a manual search of the references mentioned in the studies and gray literature was done. The literature search yielded a total of 157 studies through a search in the electronic database PubMed. Among all the studies, 51 duplicate records were removed. Ninety-seven studies were removed after screening of titles and abstracts. A total of 9 studies were included for full-text reading. Five studies were included (one randomized single-blind study, two randomized double-blind split-mouth studies, and two randomized clinical trials) in the review. Four out of five studies that were included in this review demonstrated a positive impact of PBMT on reducing pain, especially during the post-operative period compared to other non-surgical treatment protocols. Photo-biomodulation therapy demonstrated an overall positive impact on reducing postoperative complications like edema and trismus.